Recent Advances in Power-to-X Technology for the Production of Fuels and Chemicals - Rego de Vasconcelos, Bruna; Lavoie, Jean-Michel (Frontiers in Chemistry, 2019)
Environmental issues related to greenhouse gas emissions are progressively pushing the transition towards fossil-free energy scenario, in which renewable energies such as solar and wind power will unavoidably play a key role. However, for this transition to succeed, significant issues related to renewable energy storage have to be addressed. Power-to-X (PtX) technologies have gained increased attention since they actually convert renewable electricity to chemicals and fuels that can be more easily stored and transported. H2 production through water electrolysis is a promising approach since it leads to the production of a sustainable fuel that can be used directly in hydrogen fuel cells or to reduce carbon dioxide (CO2) in chemicals and fuels compatible with the existing infrastructure for production and transportation. CO2 electrochemical reduction is also an interesting approach, allowing the direct conversion of CO2 into value-added products using renewable electricity. In this review, attention will be given to technologies for sustainable H2 production, focusing on water electrolysis using renewable energy as well as on its remaining challenges for large scale production and integration with other technologies. Furthermore, recent advances on PtX technologies for the production of key chemicals (formic acid, formaldehyde, methanol and methane) and fuels (gasoline, diesel and jet fuel) will also be discussed with focus on two main pathways: CO2 hydrogenation and CO2 electrochemical reduction.